(untitled) - McKenzie, Richard B.; Richard B. McKenzie; Dwight R. Lee (New York, 1998)
Generously illustrated with examples from business, industry, government, academia, and professional sports, this superb volume offers a comprehensive overview of incentives, both in theory and in practice, providing a wealth of ideas managers can use to get employees to work harder, smarter, and more cooperatively. Much of the book is quite eye-opening. For instance, while McKenzie and Lee recognize that money is the prime motivator, they urge managers not to overlook the power of non-monetary incentives, carefully evaluating such motivators as fringe benefits, psychological incentives, education, and training. And they examine a host of other issues, including how to take advantage of executive "overpayment" to increase profits; the limits of piece-rate and other pay-for-performance schemes; finding the right balance between current pay and a more generous pension plan; the value of tough bosses; and hostile takeovers as a form of managerial incentive
Includes bibliographical references (p. [299]-329) and index
Keywords: Industrial management; Incentives in industry; Employee motivation; Incentives (Psychology); Motivation (Psychology)